Effects of the Predominant Pulse on the Inelastic Displacement Ratios of Pulse-Like Ground Motions Based on Wavelet Analysis - Guochen Zhao; Jingzhou Zhu; Xingji Zhu; Longjun Xu (Advances in Civil Engineering)
Having a predominant pulse is the main feature for pulse-like ground motions differing from others. To investigate the influence of the predominant pulse on the inelastic displacement ratios of pulse-like ground motions, the wavelet analysis method is used to extract the predominant pulse. The results indicate that the inelastic displacement ratios of the pulse-removed parts obtained by subtracting the extracted pulse from the original pulse-like ground motions are close to the results of non-pulse-like ground motions. The ratio of the energy of the extracted pulse to the energy of the original ground motion is used to represent the pulse intensity. The results indicate that the pulse period determines the locations in which the inelastic displacement ratios would have noticeable increments, and the pulse intensity determines the degree of the increments. Besides, the effects of five commonly used parameters (PGV, PGD, PGV/PGA, Arias intensity Ia, and soil condition) on the inelastic displacement ratios of pulse-like ground motions and their relations to the pulse period and the pulse intensity are studied. Finally, a new model, in which the influence of pulse intensity is considered, to predict the inelastic displacement ratios of pulse-like ground motions is proposed.